Inorganic fertilizer trials on P. radiata and P. pinaster in the Western Cape - Glen, Lauchlan McKinnon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1973.